2022
DOI: 10.1186/s12909-022-03225-w
|View full text |Cite
|
Sign up to set email alerts
|

Motivations, barriers, and professional engagement: a multisite qualitative study of internal medicine faculty’s experiences learning and teaching point-of-care ultrasound

Abstract: Background Point-of-care ultrasound (POCUS) graduate medical education is expanding across many specialties, but a lack of trained faculty is a common barrier. Even well-designed faculty development programs struggle with retention, yet little is known about the experiences of practicing physicians learning POCUS. Our objective is to explore the experiences of clinician-educators as they integrate POCUS into their clinical and teaching practices to help inform curriculum design. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…In line with these findings, our students reported feeling connected and refreshed by their participation in the elective, particularly the hands-on scanning component. Overall, the results from our students’ experiences and perceptions of POCUS mirror trends reported in the literature [ 3 , 15 , 54 , 67 , 71 ].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In line with these findings, our students reported feeling connected and refreshed by their participation in the elective, particularly the hands-on scanning component. Overall, the results from our students’ experiences and perceptions of POCUS mirror trends reported in the literature [ 3 , 15 , 54 , 67 , 71 ].…”
Section: Discussionsupporting
confidence: 85%
“…While participant enjoyment of educational experiences, including satisfaction with the course content, resources, and instructors, is not essential for learning to occur, it is linked with higher quality learning outcomes and improved psychological well-being [ 53 , 69 , 70 ]. Moreover, training in POCUS has been shown to promote engagement, and combat burnout in students and practitioners [ 68 , 70 , 71 ]. In line with these findings, our students reported feeling connected and refreshed by their participation in the elective, particularly the hands-on scanning component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinicians report the use of POCUS gives them more time in direct contact with patients, is interesting to learn and conduct, and garners positive feedback from trainees, all of which were suggested to reduce concerns for burnout. 33 …”
Section: Define the Problemmentioning
confidence: 99%
“…As the utilization of US expands, there has been an impetus to incorporate an US curriculum at the undergraduate medical education level (6)(7)(8)(9) in order to improve comprehension of anatomy, as well as accuracy of the physical examination (2,(10)(11)(12)(13). Previous studies have demonstrated a better understanding of musculoskeletal (MSK) and cardiac anatomy/physiology when US was used as a teaching tool (14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%